Draft genome sequence of a multidrug-resistant Chryseobacterium indologenes isolate from Malaysia - Yu, C.Y.; Ang, G.Y.; Cheng, H.J.; Cheong, Y.M.; Yin, Wai Fong; Chan, Kok Gan (Elsevier, 2016)
Chryseobacterium indologenes is an emerging pathogen which poses a threat in clinical healthcare setting due to its multidrug-resistant phenotype and its common association with nosocomial infections. Here, we report the draft genome of a multidrug-resistant C. indologenes CI_885 isolated in 2014 from Malaysia. The 908,704-kb genome harbors a repertoire of putative antibiotic resistance determinants which may elucidate the molecular basis and underlying mechanisms of its resistant to various classes of antibiotics. The genome sequence has been deposited in DDBJ/EMBL/GenBank under the accession number LJOD00000000.